Tingkat Pengetahuan dan Dukungan Suami dengan Perilaku Deteksi Dini Kanker Serviks di Banjar Kutuh Kelod - Juniastini, Ni Wayan Eva Juniastini Eva; Muliawati, Ni Kadek; Lestari, Ni Kadek Yuni Lestari Yuni; Puspawati, Ni Luh Putu Dewi (Universitas Baiturrahim, 2025)
Cervical cancer is still a major health problem in Indonesia. This research aims to determine the relationship between husbands' level of knowledge and support and wives' behavior in early detection of cervical cancer in Br Kutuh Kelod, Ubud, which was conducted in October-December 2023. Analytical survey research with a cross-sectional approach. using purposive sampling technique totaling 86 people. Data collection used questionnaires and data analysis using the Chi Square test with the results obtained that 39(45.3%) of respondents had a good level of knowledge and the majority of respondents had good support from their husbands to carry out early detection examinations for cervical cancer, namely 49(57%). %) respondents. Most of the respondents had been screened for cervical cancer, namely 57 (66.3%) respondents. The results of the bivariate analysis of the level of knowledge obtained a P-value = 0.001 (<0.05) while for husband's support the value was P-value = 0.000 (<0.05), which means that there is a significant relationship between the level of knowledge and husband's support for behavior. wife in early detection of cervical cancer. For health workers, expand the target of health promotion to husbands or fathers so that later they can also support their married wives or daughters to undergo early detection examinations for cervical cancer.